2016
DOI: 10.1007/s00405-016-4088-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of xenogenic acellular dermal matrix in reconstruction of oncological hypopharyngeal defects

Abstract: Acellular dermal matrix (ADM) can be used as a new membrane substitute for repairing mucosal defects. The objective of this study is to explore the effectiveness of xenogenic acellular dermal matrix (xeno-ADM) in hypopharynx reconstruction. A total of 40 patients were treated with this surgical method to reconstruct hypopharynx in our department between February 2011 and October 2012. Patients were diagnosed had hypopharyngeal cancer located at lateral and/or postpharyngeal wall. The mucosal defect size after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This was also consistent with the results of other previous studies on ADM repair. [ 27 , 28 ] The reason for this might be that the ADM retains collagen fibers, elastic fibers, and reticular fibers in the original dermis, forming the material basis for soft texture, lighter contraction, and lighter color change after the survival of ADM graft. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also consistent with the results of other previous studies on ADM repair. [ 27 , 28 ] The reason for this might be that the ADM retains collagen fibers, elastic fibers, and reticular fibers in the original dermis, forming the material basis for soft texture, lighter contraction, and lighter color change after the survival of ADM graft. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the use of xeno-ADM saves time and reduces blood loss, which is also supported by the conclusions of other previous studies. [ 27 , 30 ] In this study, the survival and recurrence rates within 1 year after operation were evaluated, and the results revealed that no patients had local recurrence in both groups. We believed that a good and sufficient repair material was conducive for adequate resection of lesions and ensure adequate safety of margins during operation.…”
Section: Discussionmentioning
confidence: 99%
“…19 The ADM has been used in thyroid cancer, laryngeal cancer, hypopharyngeal cancer, and tympanic membrane repair. 7,18,20,21 The advanced spatial structure of type I collagen is retained in the ADM, and the microstructure of collagen is more complete. Three-dimensional structures can provide excellent scaffolds for cell crawling, and the presence of microstructure promotes cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…17 The simple native biomaterials such as allogeneic acellular dermal matrix patches are only used to repair a small range of defects. [18][19][20] In our experiment, the complex full-thickness ECM with vascular pedicle scaffold was prepared to solve the large scale of hypopharyngeal defects and has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%